Case Study 4 - Indonesia : Participatory Approaches in Budgeting and Public Expenditure Management - World Bank (Washington, DC, 2012)
Following a dramatic drop in per capita GNP from US$ 1200 in early 1997 to US$ 680 in 1998, the Indonesian government began implementing social safety net (SSN) programs targeting the adversely affected - those who became poor after the crisis and everyone already living in poverty. These were aimed at supplementing their purchasing power through the Special Market Operation (OPK) of subsidized rice distribution, preserving access to critical social services such as education through student scholarships, and augmenting incomes through labor intensive employment opportunities. To monitor the implementation of these SSN programs and to provide donors and government with qualitative information about the social impacts of the 1997 financial crisis, the World Bank formed the Social Monitoring and Early Response Unit (SMERU) with major assistance from AusAid, Asia-Europe Meeting Fund, and USAID. SMERU has five different units with tasks of, i) building local capacity for rapid assessments of potential 'danger' situations in the field, ii) forming a network of networks of NGOs for information exchange at all levels, iii) building capacity of communities to do their own monitoring, iv) storing and analyzing quantitative and qualitative data, and v) conducting a study on the impact of provincial trade deregulation. CBM is thus just one of the five units responsible for one of the core mandates of SMERU.